Gravity anomalies and segmentation of the Eastern USA passive continental margin - Wyer, P; Wyer, Paul Patrick Andrew (2003)
﻿ A compilation of high quality post-rift sediment isopach data has been used in conjunction with the observed free-air gravity anomaly to determine segmentation of the long term mechanical properties of the lithosphere at the Eastern USA passive margin. This segmentation is represented by a process-oriented analysis in which the flexural response of the margin to post-rift sediment loading is controlled by spatial variations in effective elastic thickness (Te) of the underlying lithosphere. Existing Eastern USA margin Te estimates range from less than 10km to more than 30km. In this study it is shown that high strengths of 10 - 40km Te are confined to structural arches dividing the broadest marginal basins, while low strengths of less than 10km Te are typically found in structural embayments and beneath the deep basins. The hinge zone, across which the degree of continental thinning increases rapidly, marks the transition between high and low strength. Yield strength envelope models support an argument that regions of low strength were created by lithospheric thinning during rifting, and sustained by thermal insulation and flexural curvature associated with voluminous post-rift sediment deposition. Along-strike Te variations - reflected in the alternation of basement platforms and embayments - are attributed to inheritance of lithospheric segmentation from earlier tectonic events. Along-strike segmentation of the margin has previously been observed as a 300 - 500km wavelength spectral energy peak in the shelf break Airy isostatic gravity anomaly (IGA) high. That this segmentation is explained by variations in the underlying lithospheric strength is demonstrated by a flexural IGA high in which the equivalent spectral peak is absent. The spectral energy of the along-strike Te distribution peaks in the same waveband. Removal of process-oriented components from the observed free-air gravity anomaly reveals other contributions that were not resolved in earlier studies. In particular, the (previously unknown) Carolina Trough Isostatic Gravity Anomaly, has been identified and attributed to an extrusive (syn-rift) volcanic source. Detailed study of this anomaly suggests that the margin is segmented in terms of its volcanic character, and argues against recent estimates of the volume of new igneous material emplaced during rifting.